Searching an ex situ collection of wheat genetic resources - Gollin, Douglas; Smale, Melinda; Skovmand, Bent (Wiley, 2000)
A theoretical model is developed and applied to the search for disease and pest resistance in ex situ collections of wheat genetic resources, employing actual data on frequency distributions, disease losses, and search costs. Experiments developed from case studies clarify several misperceptions about the value of gene banks and their utilization by breeders. The observation that wheat breeders “use” gene banks rarely does not imply that marginal accessions have low value. High costs of transferring genes with conventional breeding techniques mean that it may be efficient to store certain categories of genetic resources (such as landraces) “unused” for many years.